A COMPARISON OF NUTRITIONAL KNOWLEDGE AND FOOD HABITS OF COLLEGIATE AND NON-COLLEGIATE ATHLETES - Hamid Arazi; Rastegar Hosseini (University of Banja Luka, Faculty of physical education and sport, 2012)
Nutrition is an important component of any physical fitness program. The main dietary goal for active individuals is to obtain adequate nutrition to optimize health fitness and to increase sports performance. The purpose of this study was to compare nutritional knowledge and food habits in collegiate s and non-collegiate athletes. The target population of this study was all male and female collegiate and non-collegiate athletes in Rasht city of Iran. After translate of the standard nutrition knowledge and attitudes survey questionnaire Zawila et al., and adjust of some questions, questionnaire was evaluated by Professors of faculty of physical education and sport sciences. The reliability guided Cronbach Alpha value of .81. A researcher-built questionnaire which was developed to measure subject's nutrition knowledge and habits, distributed to 130 collegiate and non-collegiate athletes males and 120 Collegiate and non- collegiate athletes females randomly. The questionnaire contained 15 nutrition knowledge questions and 25 nutrition habits questions. The collected data was analyzed by t-test, one-way ANOVA and Pearson correlation coefficient (p < .05). The correct response rate for the sport nutrition and general nutrition score were in collegiate athletes male (57.15; 52.5%) and athletes female (58.14; 54.85%); non-collegiate athlete's males (41.55; 39.86%) and athletes female (42.11; 40.66 %) respectively. Also, mean nutrition scores in collegiate athlete's males and females were significantly higher than non-collegiate athletes male and females. Furthermore, there were significant differences in the total mean score questionnaire between collegiate and non- collegiate athletes (p < .05). Based on the result of our study the knowledge of Iranian non-collegiate athletes were lower than collegiate athlete. For this reason, nutrition knowledge and attitudes of Iranian non-collegiate athletes need to improve. So, these suggest that nutrition lectures' courses is one of the solutions to increase knowledge about nutrition.